Evaluasi Perhitungan Volume Stockpile Batubara dengan menggunakan Alat Total Station di PT. Bukit Baiduri Energi, Kabupaten Kutai Kartanegara, Provinsi Kalimantan Timur - Muhammad Rofy Fauzan; Henny Magdalena; Lucia Litha Respati; Windhu Nugroho; Albertus Juvensius Pontus (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Coal stockpile volume measurement is an essential part of mining production control. This study aims to evaluate the calculation of coal stockpile volume using a Total Station (TS) at PT. Bukit Baiduri Energi, Kutai Kartanegara Regency, East Kalimantan Province, and to assess the accuracy and effectiveness of this method in operational activities. Data acquisition was carried out through direct field measurements using a Total Station with a detailed surface point survey method. The collected data were processed using Minescape 5.7 software to generate a triangulated surface model, and the volume was calculated using the Cut and Fill method. The results show that the Total Station method produced a stockpile volume of 21,069.15 m³ with a high level of accuracy due to direct field measurement. This method provides advantages in elevation data accuracy; however, it requires relatively more time and manpower during the data acquisition process. Based on these findings, the use of Total Station is recommended for stockpile volume calculations that require high accuracy, particularly for production evaluation and coal reserve reporting.